ANALISIS KESALAHAN PENGGUNAAN KATA KETERANGAN MENGULANG â€œHAIâ€DANâ€œZAIâ€ PADA MAHASISWA ANGKATAN 2016 PROGRAM STUDI PENDIDIKAN BAHASA MANDARIN FKIP UNIVERSITAS TANJUNGPURA - Oktavianusa, Oktavianusa; Thamrin, Lily; Lusi, Lusi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractChinese adverbs are an important part of the word class, the most commonly used adverbs are return and again. For Chinese learning, it is difficult to learn the adverbs return and again. Because these two words are used in different ways and have different meanings, they are often misused in use. This paper tests and analyzes the use of the adverbs return and again in the 2016 chinese language major of the teachers college of teacher education at the national university of tanjung pura. It is concluded that the 2016 chinese students of the Danish brass college of teacher education have used the adverb return and again to be more biased than the return. The types of errors are misdirected and misaligned. The reason for the bias is that the students are affected by negative transfer of the mother tongue and negative transfer of the target language. Keywords: Compound directional complement, Errors analysis, Reasons for errors